Age‐disparate sex and HIV risk for young women from 2002 to 2012 in South Africa. Issue 1 (26th December 2016) - Evans, Meredith; Risher, Kathryn; Zungu, Nompumelelo; Shisana, Olive; Moyo, Sizulu; Celentano, David D; Maughan‐Brown, Brendan; Rehle, Thomas M
Abstract : Introduction : Age‐disparate sex has long been considered a factor that increases HIV risk for young women in South Africa. However, recent studies from specific regions in South Africa have found conflicting evidence. Few studies have assessed the association between age‐disparate partnerships (those involving an age gap of 5 years or more) and HIV risk at the national level. This study investigates the relationship between age‐disparate sex and HIV status among young women aged 15–24 in South Africa. Methods : Nationally representative weighted data from the 2002, 2005, 2008, and 2012 South African National HIV Surveys were analysed for young women aged 15–24 years using bivariate analyses and multiple logistic regressions. Results : After conducting multiple logistic regression analyses and controlling for confounders, young women with age‐disparate partners had greater odds of being HIV positive in every survey year: 2002 (aOR = 1.74, 95%CI: 0.81–3.76, p = 0.16); 2005 (aOR = 2.11, 95%CI: 1.22–3.66, p < 0.01); 2008 (aOR = 2.02, 95%CI: 1.24–3.29, p < 0.01); 2012 (aOR = 1.53, 95%CI: 0.92–2.54, p < 0.1). The odds of being HIV positive increased for each year increase in their male partner's age in 2002 (aOR = 1.10, 95%CI: 0.98–1.22, p = 0.11), 2005 (aOR = 1.10, 95%CI: 1.03–1.17, p < 0.01), 2008 (aOR = 1.08, 95%CI: 1.01–1.15, p < 0.05), and 2012 (aOR = 1.08, 95%CI: 1.01–1.16, p < 0.05). Findings were statistically significant (p < 0.1) for the years 2005, 2008, and 2012. Conclusions : Our findings suggest that age‐disparate sex continues to be a risk factor for young women aged 15–24 in South Africa at a national level. These results may reflect variation in HIV risk at the national level compared to the differing results from recent studies in a demographic surveillance system and trial contexts. In light of recent contradictory study results, further research is required on the relationship between age‐disparate sex and HIV for a more nuanced understanding of young women's HIV risk.